Highly sensitive switching of solid-state luminescence by controlling intersystem crossing - Weijun Zhao (Nature Portfolio, 2018)
The development of intelligent materials, in particular those showing the highly sensitive mechanoresponsive luminescence (MRL), remains challenging. Here the authors report a strategy for constructing high performance On-Off MRL materials by introducing nitrophenyl groups to molecules with aggregation-induced emission characteristic.